Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Guru: The Influence of Leadership and Work Motivation on Performance Teacher - apan apan (Jurnal Bisnis dan Ekonomi, 2026)
Objective : This study examines the influence of school leadership and work motivation on teacher performance, both individually and simultaneously, to determine the extent to which these organizational and psychological factors explain performance differences in educational institutions. Methods : A quantitative descriptive approach was employed. Data were collected through questionnaires distributed to 37 teachers and analyzed using statistical techniques to assess correlation, predictive relationships, data categorization, and instrument validity. Research Results : The results indicate that school leadership contributes 44.1% to teacher performance, while work motivation contributes 24.1%. When analyzed jointly, both variables explain 68.2% of the variance in teacher performance. These findings demonstrate that teacher performance is not determined by a single factor, but rather by the combined and complementary effects of effective leadership and strong work motivation.